Efektivitas PBL terhadap Pemahaman Konsep Fisika pada Materi Besaran dan Satuan - Iza Elcani Gurning; Deswalman Deswalman (Seminar Nasional Teknologi dan Multidisiplin Ilmu (SEMNASTEKMU), 2025)
This study examines the effectiveness of Problem Based Learning (PBL) compared to conventional instruction in improving students’ conceptual understanding of measurement in physics. Conducted in two grade X classes at SMA Negeri 10 Kota Jambi, the research applied a quasi-experimental method with a non-equivalent pretest–posttest design. Class XE1 received PBL, while class XE2 received conventional teaching. Thirty multiple-choice items were used to evaluate conceptual understanding before and after instruction. The normalized gain (N-gain) was employed to measure learning improvements. The experimental class obtained an N-gain of 0.718 (high), whereas the control class obtained 0.556 (medium). These findings indicate that PBL enhances conceptual understanding more effectively through collaborative problem-solving, analysis, and reflection. In contrast, teacher-centered conventional instruction offers fewer opportunities for conceptual construction. PBL is recommended for broader implementation in physics learning.